PENERAPAN MODEL PEMBELAJARAN KOOPERATIF FORMULATE SHARE LISTEN CREATE (FSLC) UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KESETIMBANGAN ION DAN PH LARUTAN PENYANGGA - Karina Dilla Mustika; Elva Yasmi Amran; Betty Holiwarni (Jurnal Pendidikan Kimia Universitas Riau, 2021)
The research is aimed to improve student learning achievement on the subject of equilibrium ion and pH buffer solution in class XI MIA SMAN 1 Pekanbaru. This type of research is an experimental study with a pretest-posttest design. The research was conducted at SMAN 1 Pekanbaru. The sample study was included class XI MIA 6 as an experimental class and class XI MIA 5 as a control class. The experimental class was applied the cooperative learning model FSLC. The data analysis technique used is the t-test. Based on the results of the data analysis test, tcount> ttable is 1.78> 1.67, meaning that the application of cooperative learning model FSLC can improve student learning achievement on the subject of equilibrium ion and pH buffer solution in class XI MIA of SMA Negeri 1 Pekanbaru.